2021
DOI: 10.1186/s40168-021-01011-2
|View full text |Cite
|
Sign up to set email alerts
|

The association between obesity and weight loss after bariatric surgery on the vaginal microbiota

Abstract: Background Obesity and vaginal microbiome (VMB) dysbiosis are each risk factors for adverse reproductive and oncological health outcomes in women. Here, we investigated the relationship between obesity, vaginal bacterial composition, local inflammation and bariatric surgery. Methods Vaginal bacterial composition assessed by high-throughput sequencing of bacterial 16S rRNA genes and local cytokine levels measured using a multiplexed Magnetic Luminex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 91 publications
1
26
0
Order By: Relevance
“…In addition, BV has also been associated with increased rates of sexually transmitted infections and pregnancy complications, including preterm birth (6,7,31). A recent study looked at Lactobacillus dominance in the vaginal microbiome among women with obesity following bariatric surgery and noted a significant increase in Lactobacillus dominance among women who experienced significant weight loss postsurgically (32).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BV has also been associated with increased rates of sexually transmitted infections and pregnancy complications, including preterm birth (6,7,31). A recent study looked at Lactobacillus dominance in the vaginal microbiome among women with obesity following bariatric surgery and noted a significant increase in Lactobacillus dominance among women who experienced significant weight loss postsurgically (32).…”
Section: Discussionmentioning
confidence: 99%
“…The IM works as an organ of the human body, whose various functions can suffer alterations if not nourished correctly 14 , 16 , 17 . Its main activities are related to the immune system, helping in the intestinal barrier, metabolism, nutrient absorption, vitamin synthesis, defense against pathogens, and the dehydroxylation of bile acid.…”
Section: Discussionmentioning
confidence: 99%
“…Obese individuals often have the microbiota associated with a decrease in Bacteroidetes and an increase in Firmicutes , but some studies in humans have found an opposite ratio, suggesting that the Firmicutes-Bacteroidetes ratio would be increased. Low MGR in obese people is associated with metabolic diseases, inflammation, and insulin resistance 16 , 17 . IM may contribute to obesity in some ways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations